AMROBS: All-Metal Replicas of Biological Surfaces—A Novel Approach Combining Established Techniques - Florian Hischen; Mirjana Keser; Werner Baumgartner (Biomimetics, 2018)
Biomimetic work often concerns to biological surfaces and their interaction with the environment. Liquid handling, barrier function and protection against heat, pathogens and predators, to name just a few, require biological surfaces to exhibit specific material properties—properties that often are not suited for specific measurements under lab conditions. In particular, the lack of the necessary sample toughness or conductivity can prove difficult to perform certain experiments. Hence, we present a novel approach to achieve all-metal replicas from biological surfaces (AMROBS). Resulting replicas exhibit microscale accurate replication of morphological topography while providing tough, conductive subjects for investigation and easy chemical surface modification. Combining established techniques like polymer casting (e.g., silicone), chemical silver precipitation and electroplating, all-metal replicas of several technical and biological surfaces (e.g., diffraction foils, lizard skin, flat bug surface) were produced and compared to their original counterparts with regard to morphology and functionality. By using scanning electron microscopy and video analysis, we show that a high degree of replication accuracy is achievable, and conclude the future possibilities of AMROBS in a comprehensive discussion, including the general “do’s” and “do nots” of metal replication following this approach.